Inflammatory cytokines and stroke and its subtypes: a genetic correlation and two-sample Mendelian randomization study - Guo, Yu; Sun, Huaiyu; Hou, Shuai; Zhang, Wuqiong; Liu, Huiqing; Zhu, Lixia; Meng, Hongmei (Frontiers in Molecular Neuroscience, 2023)
Introduction The causal relationship between inflammatory factors and stroke subtypes remains unclear. This study aimed to analyze the causal relationship between 41 inflammatory factors and these two factors using Mendelian randomization (MR). Methods We performed a two-sample MR analysis to assess the causal effects of 41 inflammatory cytokines on stroke and its subtypes and conducted a genome-wide association study (GWAS) data. The inverse-variance weighted (IVW) method was adopted as the main MR method, and we performed a series of two-sample Mendelian randomizations and related sensitivity analyses. Results The study indicated some suggestive evidences: using the IVW approach, we found that lower possible levels of IL-4 were positively associated with the occurrence of stroke (odds ratio [OR] = 0.93, 95% confidence interval [CI]: 0.88–0.99, p = 0.014), higher interleukin (IL)-1β, IL-12p70 levels may be positively correlated with the occurrence of stroke (OR = 1.09, 95% CI: 1.01–1.18, p = 0.027; OR = 1.08, 95% CI: 1.02–1.15, p = 0.015). For IS, results showed that lower levels of IL-4, tumor necrosis factor-related apoptosis-inducing ligand were positively associated with the occurrence of possible ischemic stroke (IS) (OR = 0.92, 95% CI: 0.87–0.98, p = 0.006; OR = 0.95, 95% CI: 0.91–1.00, p = 0.031), higher levels of IL-1β, IL-12p70 and vascular endothelial growth factor (VEGF) may be positively correlated with the occurrence of IS (OR = 1.09, 95% CI: 1.00–1.19, p = 0.042; OR = 1.07, 95% CI: 1.01–1.15, p = 0.035; OR = 1.06, 95% CI: 1.00–1.12, p = 0.034). Our findings suggest that decreased IL-17 levels could potentially be linked to a higher likelihood of intracerebral hemorrhage (ICH) (OR = 0.51, 95% CI: 0.28–0.93, p = 0.028). For subtypes of stroke, IS and ICH, higher levels of growth regulated oncogene-α, beta nerve growth factor, IL-18, macrophage colony-stimulating factor, and induced protein 10 upregulated the risk factors while lower levels of IL-2ra and IL-17 upregulated the risk factors. Conclusion In summary, our research validated that inflammatory markers have a pivotal impact on the development of stroke and could potentially offer a fresh approach to treating this condition.